2007
DOI: 10.1037/1931-3918.1.2.116
|View full text |Cite
|
Sign up to set email alerts
|

Applying for the predoctoral internship: Training program strategies to help students prepare.

Abstract: The predoctoral internship signifies the culmination of applied training in professional psychology. With the increasing supply and demand gap, securing an internship has become competitive and has resulted in many students employing a wide variety of steps in an attempt to ensure a successful internship application. However, little is known about how academic training programs assist students in applying for an internship. The purpose of this study was to describe what activities training programs engage in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 16 publications
0
13
1
Order By: Relevance
“…Applicants spend a great deal of time and energy (Madson, Aten, & Leach, 2007) trying to get the ''right'' experiences. Publications (WilliamsNickelson, Prinstein, & Keilin, 2008) and journal articles (Lopez & Draper, 1997;Mellott, Arden, & Cho, 1997) have discussed options and strategies to help students find the right program for their training.…”
mentioning
confidence: 99%
“…Applicants spend a great deal of time and energy (Madson, Aten, & Leach, 2007) trying to get the ''right'' experiences. Publications (WilliamsNickelson, Prinstein, & Keilin, 2008) and journal articles (Lopez & Draper, 1997;Mellott, Arden, & Cho, 1997) have discussed options and strategies to help students find the right program for their training.…”
mentioning
confidence: 99%
“…According to this perspective, trainees have the only objective of finishing the experience as soon as possible and are content to carry out activities, even if these have nothing to do with psychology (Olver et al, 2011). According to Madson, Aten, and Leach (2007), students who devalue their training think that they might have some learning opportunities only if they are offered by the tutor.…”
Section: Discussionmentioning
confidence: 99%
“…The educational purpose of fieldwork in criminal justice is to develop awareness of students' values and attitudes towards the criminal justice system and the community, to learn to work with the agency's clients, and to provide experience that is beneficial for obtaining employment in the future (Taylor, 2012). The ways in which academic training programs assist students in applying for an internship are still largely unknown (Madson, Aten, & Leach, 2007). Few studies have addressed the important elements of professional skills and psychological preparation for fieldwork in criminal justice settings.…”
Section: Introductionmentioning
confidence: 99%
“…As studies have suggested (Madson, Aten, & Leach, 2007), students find the application process to be stressful and anxiety provoking. Moreover, waiting for decisions regarding field placement is a process filled with anxiety and uncertainty.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation